2012
DOI: 10.1021/cb300193f
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Allergen Design Reveals the Significance of Moderate Affinity Epitopes in Mast Cell Degranulation

Abstract: This study describes the design of a well-defined homotetravalent synthetic allergen (HTA) system to investigate the effect of hapten-IgE interactions on mast cell degranulation. A library of DNP-variants with varying affinities for IgEDNP was generated (Kds 8.1 nM – 9.2 µM), and 8 HTAs spanning this range were synthesized via conjugation of each DNP-variant to the tetravalent scaffold. HTAs with hapten Kds < 235 nM stimulated degranulation following a bell-shaped dose response curve with maximum response occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 36 publications
(84 reference statements)
3
31
0
Order By: Relevance
“…Through a combination of experimental approaches and molecular modeling, it has been demonstrated that the average distance between the two Fab domains of IgE is 11–13 nm and that, owing to the differences between the extended and in-solution length of ethylene glycol, a PEG 3350 linker (extended length of 29 nm) is required to span the two antigen-binding sites on a single IgE 2628 . Previously, we identified that ethylene glycol with an extended length of ∼6 nm is optimal for haptens to bind multiple antibodies without bridging the two antigen-binding sites on a single antibody 2933 . Consequently, in our tetravalent allergen design, the four hapten moieties were conjugated to the core of the molecule with 8 units of ethylene glycol, which provided an extended length of 3.2 nm, yielding a maximum separation of 6.4 nm between haptens (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Through a combination of experimental approaches and molecular modeling, it has been demonstrated that the average distance between the two Fab domains of IgE is 11–13 nm and that, owing to the differences between the extended and in-solution length of ethylene glycol, a PEG 3350 linker (extended length of 29 nm) is required to span the two antigen-binding sites on a single IgE 2628 . Previously, we identified that ethylene glycol with an extended length of ∼6 nm is optimal for haptens to bind multiple antibodies without bridging the two antigen-binding sites on a single antibody 2933 . Consequently, in our tetravalent allergen design, the four hapten moieties were conjugated to the core of the molecule with 8 units of ethylene glycol, which provided an extended length of 3.2 nm, yielding a maximum separation of 6.4 nm between haptens (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we selected DNP/IgE DNP as the high affinity pair in our design. The hapten DNP can be chemically modified to alter the affinity of this interaction to generate weaker affinity pairs [17, 24]. In order to create a second hapten/IgE pair with weaker affinity, we synthesized a DNP variant, DNP-proline (DNP-Pro).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we describe the design, synthesis, and characterization of synthetic tetravalent allergens (Handlogten et al, 2013; Handlogten et al, 2012; Handlogten et al, 2013). These well-defined tetravalent allergens have several advantages compared to the widely used haptenated proteins, such as DNP conjugated to BSA (DNP-BSA), as model allergens.…”
Section: Resultsmentioning
confidence: 99%
“…We previously established that the relative concentration of each IgE in solution is preserved on the surface of the mast cells (Handlogten et al, 2012). The mast cells were then exposed to mixtures of HmTA [DNP 4 ] and HmTA [dansyl 4 ] with concentrations ranging from 0.5 nM to 1000 nM (Figure 3, Figure S2).…”
Section: Resultsmentioning
confidence: 99%